PERILAKU DAN KETAHANAN STRUKTUR RUMAH VERNAKULAR DESA GUNUNG ALAM LEBONG TERHADAP GEMPA BUMI - Bahri, Samsul; Hanif, muhammad Fauzan; Islam, Mukhlis; Prihatiningrum, atik (Inersia: Jurnal Teknik Sipil, 2022)
Lebong Regency is an earthquake-prone area in Bengkulu Province. This is because Lebong Regency is located adjacent to the Bukit Barisan Mountains which are included in the earthquake-prone zone and in the line of active faults. This research was conducted at Mr. Sonid’s vernacular house in Gunung Alam Village, Pelabai District, Lebong Regency to determine the behavior and the resistance of its structure.The behavior and resilience of the vernacular house structure against earthquakes is analyzed based on SNI 1726:2019. The analysis was carried out using SAP 2000 software to obtain the actual internal forces in the form of bending moment (M), shear force (V), and compressive force (P).The capacity of the wood structure was analyzed using the Load and Resistance Factor Design (LRFD) method which refers to SNI 7973:2013 to obtain adjusted moment capacity values (M'), adjusted compression capacity (P'), and adjusted shear capacity (V').The results of structural analysis of earthquakes produce the same actual internal forces in medium and soft soil conditions so that all structural elements of the vernacular house have the same structural behavior.Analysis of the capacity of the wooden structure results the adjusted internal forces of some structural elements which are smaller than the actual internal forces, so that the vernacular house structure is unable to withstand the forces that occur. However, based on the earthquake and its impact until this research was conducted, the condition of the vernacular house still stands strong without any damage to its structural elements.